Pengaruh Promosi dan Inovasi Produk Terhadap Minat Beli Honda Scoopy (Studi Kasus Pada PT. Tunas Dwipa Matra Diwek, Jombang) - Dwi Agustin; Rohmad Prio Santoso (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2023)
The purpose of this research is to understand and provide an understanding regarding the influence of promotion and product innovation on buying interest of Honda Scoopy at PT. Tunas Dwipa Matra Diwek, Jombang. This study applies a quantitative approach. This study utilizes a saturated sample to sample the entire population, which consists of 68 respondents. Studies show that: (1) Promotion has a positive and significant influence on the intention to buy a Honda Scoopy at PT. Tunas Dwipa Matra Diwek, Jombang. (2) Product innovation has a positive and significant influence on the intention to buy a Honda Scoopy at PT Tunas Dwipa Matra Diwek, Jombang. (3) Product Promotion and Innovation simultaneously have a positive and significant influence on the intention to buy Honda Scoopy at PT. Tunas Dwipa Matra Diwek, Jombang.